Metode Penelitian Ilmiah Isolasi dan Identifikasi Bakteri Asam Laktat dari Tempoyak Tradisional Asal Jambi - Intan Hapsari; Ardi Mustakim (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Durian is a tropical fruit belonging to the climacteric group, meaning it experiences a surge in respiration after harvest and quickly deteriorates. Due to its perishable nature, processing is necessary to extend its shelf life and maintain its nutritional value and flavor. One traditional method of processing that has long been known in Indonesia, particularly in Kalimantan and Sumatra, is the fermentation of durian flesh into tempoyak. Tempoyak is a natural fermentation product made from ripe durian flesh that has undergone a further ripening process and has a distinctive sour taste and strong aroma. The tempoyak fermentation process involves the activity of microorganisms, particularly lactic acid bacteria (LAB) such as Lactobacillus plantarum and Lactobacillus curvatus, which play a crucial role in producing flavor, a semi-solid texture, and functional health benefits. Human food needs depend not only on the quantity of food but also on the quality of its nutritional content, such as carbohydrates, protein, fat, vitamins, and minerals. In this context, fermented foods such as tempoyak provide added value in the form of probiotics that have the potential to improve digestive health. Lactic acid bacteria, which dominate the natural fermentation process, play a crucial role in the formation of flavor compounds and beneficial biological activities. This study aimed to isolate and identify the types of LAB present in traditional tempoyak from Jambi. Isolation was conducted to obtain pure strains of bacteria with potential probiotics, while identification aimed to determine the dominant bacterial species in the tempoyak fermentation process. The results of this study are expected to contribute to the development of functional food products based on local fermentation.